The Increase of the Electrophoretic Mobility of Platelets after Laparotomy - Yamazaki, Hiroh; Tsukui, Ryoko; Motomiya, Takeshi; Jung, Stephanie May; Sonoda, Minoru; Watanabe, Chifuyu; Ogino, Masahiro; Miyagawa, Noboru (Thrombosis and Haemostasis, 1980)
A fully automatic instrument for the determination of electrophoretic mobility of colloidal particles was applied to human platelets. A significant increase in platelet electrophoretic mobility was observed one day after a laparotomy. This suggests that a selective consumption of platelets with smaller surface negative charge may occur during postoperative hemostatic plug formation or under surgical stress. In addition, the difference in electrophoretic mobility observed between males and females suggests an effect of estrogen on platelets.
Keywords: Electrophoretic mobility of platelets; Automatic instrument for platelet electrophoresis; Surface negative charge; Surgical stress; Laparotomy; Estrogen; Sex difference in platelets